Modifikasi Dimensi Hoax dan Negative Campaign dalam Pemilihan Umum Sebagai Wujud Pemenuhan Hak Kebebasan Berpendapat - Mahardika, Ahmad Gelora (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2024)
The election is a regular political momentum in the Indonesian constitutional system. History records that elections have always been a political contestation that presents various dynamics at the national and local levels. This dynamic has various forms, including hoax news or negative campaigns whose truth cannot be verified. However, the Indonesian legal system still needs to provide a concrete definition regarding the differentiation of meaning between insult and criticism. That causes the perpetrators of the criminal act of spreading hoaxes to be interpreted unilaterally by law enforcement even though it was criticism. On the other hand, as the supreme leader of law enforcement, the government has the potential to abuse power and intervene in law enforcement processes, which can disrupt Indonesia's democratic process in elections. Based on this, the idea of modifying the dimensions of hoaxes and negative campaigns in elections, especially related to the criminal system, is urgent. The hypothesis in this study is that it is necessary to modify the dimensions of the election, especially those governing the electoral criminal system as a form of state existence to present democratic elections.